PERILAKU KONSUMEN DALAM BERBELANJA GULA KRISTAL PUTIH DI KOTA PEKANBARU - Sri Utami Rahmasari; Yeni Kusumawaty; Eliza Eliza (Fakultas Pertanian, Universitas Riau, 2022)
People commonly consume many types of sugar. However, the type of sugar most commonly consumed by the people of Pekanbaru City is white crystal sugar or granulated sugar. This study aims to determine the characteristics of consumers of white crystal sugar and consumer habits in shopping for white crystal sugar. The method used is descriptive analysis. The number of respondents who consumed white crystal sugar was 100 people. The results showed that the characteristics of white crystal sugar consumers in Pekanbaru City could be seen in age, gender, and occupation. White crystal sugar consumers are more dominant in shopping at traditional retail than modern retail. The brand of packaged white crystal sugar consumers are most interested in is Gulaku. Consumers of white crystal sugar make a purchase of 1 kg for each purchase. The frequency of consumers purchasing white crystal sugar is once per month. Consumers mostly use branded white crystal sugar for personal consumption. For business raw materials, they mostly use bulk white crystal sugar, and for personal consumption and business raw materials in Pekanbaru City mostly use bulk white crystal sugar